Roads out of Poverty? Assessing the Links between Aid, Public Investment, Growth, and Poverty Reduction - Agénor, Pierre-Richard; Bayraktar, Nihal El; Aynaoui, Karim (World Bank, Washington, DC, 2012)
The authors develop a macroeconomic framework that captures links between aid, public investment, growth, and poverty. Public investment is disaggregated into education, infrastructure, and health, and affects both aggregate supply and demand. Dutch disease effects are captured by accounting for changes in the relative price of domestic goods. The authors assess the impact of policy shocks on poverty by linking the model to a household survey. They calibrate the model for Ethiopia and simulate the changes in the allocation of aid and public investment. The authors also calculate the amount by which foreign aid should increase to reach the poverty targets of the Millennium Development Goals.